Oficina do Conviver: preocupações prementes de adolescentes do ensino médio sob o olhar da psicologia analítica - Vasconcellos, Ana Paula Navarro de (2019)
This work aimed to identify and understand pressing and recurring concerns and emotional/behavioral problems of high school adolescents in a public school at Sao Paulo city. A sequential exploratory study using a mixed-method was carried out, with a quantitative step in which 110 adolescents responded to the YSR / 11-18 self-report instrument (Youth Self-Report) and a qualitative step in which 14 adolescents, selected from the analysis of the scales, participated of Oficina do Conviver (Living Together Workshop), a methodology using expressive/symbolic resources (paintings on hexagons) and group talk held in two meetings. The results of YSR / 11-18 indicated that 42.7% of the population studied reported the incidence of emotional/behavioral problems in the clinical range, when taking into consideration the Total Problems scale, with a higher frequency of internalizing factors and problems reported in the Anxiety/Depression scale. There were significant differences between boys and girls in Total of Problems (p = 0.012) and Internalizing Factors (p = 0.004), with the frequency of girls in the clinical range accounting for 55.8% and 67.3%, respectively. At the qualitative stage of the study, the narratives and the graphic production were analyzed, assessing concerns reported by adolescents related to school, family and affective relations, emotional states, body and sexuality, life and future. Concerns and emotional/ behavioral problems showed experiences of psychic suffering, such as sudden mood swings, feelings of loneliness, sadness, anxiety and fear, self-destructive feelings and behaviors (suicide, self-mutilation and substances use), feelings of helplessness, experiences of abuse and rape, eating disorders, and experiences related to sexuality and identity. The symbolic productions allowed the identification of unconscious aspects of the adolescents' reports and the assessment of the impacts of fantasies and autonomous complexes that erupted with symptoms of estrangement and disconnection, suggesting psychic disorders that demand attention and treatment. The study points to the need to offer psychological support in schools through creative resources aimed at caring and contributing to risk prevention and mitigation of adolescent psychic suffering